Age-stage predation capacity of Phytoseiulus persimilis and Amblyseius swirskii (Acari: Phytoseiidae) on susceptible and resistant rose cultivars. Issue 4 (18th May 2016) - Alipour, Zahra; Fathipour, Yaghoub; Farazmand, Azadeh
ABSTRACT: Predation rate is basic to any investigation of prey–predator interaction. The predation rate of Phytoseiulus persimilis Athias-Henriot and Amblyseius swirskii Athias-Henriot (Acari: Phytoseiidae) fed on the two-spotted spider mite (TSSM), Tetranychus urticae Koch, reared on the susceptible (Yellow) and resistant (Roulette) rose cultivars was determined under laboratory conditions at 25 ± 1°C, 60 ± 5% RH and a photoperiod of 16:8 (L:D) h. The value of total prey consumption in different life stages of both predators was higher on TSSM reared on the resistant rose cultivar than those on the susceptible one. In addition, the value of total prey consumption in different life stages of P. persimilis was higher than A. swirskii on both susceptible and resistant rose cultivars. The net predation rate ( C 0 ) of both predators on TSSM reared on the resistant rose cultivar was higher than those on the susceptible one. The stable predation rate ( ψ ) on the susceptible and resistant rose cultivars was 2.50 and 3.77 preys/predator for P. persimilis, respectively, and 2.24 and 2.76 preys/predator for A. swirskii, respectively. The finite predation rate ( ω ) in P. persimilis on the susceptible and resistant rose cultivars was 3.10 and 4.41, respectively, and in A. swirskii it was 2.58 and 3.10, respectively. The results revealed that the performance of both predators on the resistant cultivar (Roulette) was better than the susceptible one (Yellow), and based on the results of the finite predation rate, P. persimilis on both cultivars had higher performance compared with A. swirskii .